“The moving adverb moves; and, having moved, moves on.” Adverb placement in L1 Arabic, L2 English and L3 French - Balcom, Patricia (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 2015)
This paper describes a study that explored the acquisition of adverb placement in L3 French by learners whose L1 was Emirati Arabic and whose L2 was English. A picture-description task was developed to tap what Fassi Fehri calls the “transportability” of adverbs in Arabic. Participants were asked to write – in all three languages – up to three sentences describing nine labelled images, using all of the words on the image. While all four possible word orders were produced in all three languages, the frequencies differed depending on adverb class and on language. With imperfective adverbs, in Arabic and English the second and third responses provided different positions for the adverb (i.e., ASVO, SAVO, SVAO, SVOA); this rarely occurred in French. With measure and voice adverbs, in Arabic many second and third responses were with the verb in sentence-initial position (i.e., VSOA and VOSA); this did not occur in English or French. Transportability in the L1 and freer adverb placement with imperfective adverbs in the L2 did not transfer to the L3 at the earliest stages.